Structural Differences in the Self-determination of Upper Secondary Students with and without Disabilities in Vocational Education - Licardo, Marta; Schmidt Krajnc, Majda (Revija za elementarno izobraževanje, 2016)
The aim of the study was to analyze the differences in degree of self-determination between students with and without disabilities and to relate these differences to grade point average and gender in both groups. Students in both groups were equalized in pairs by age, gender and school program (n = 122; 61 pairs). Results indicate that students with disabilities have a lower level of self-determination than their peers without disabilities. With regards to gender, girls with disabilities have the lowest level of self-determination. An analysis of differences in self-determination by grade point average (GPA) showed that students with and without disabilities who had high GPAs have higher levels of self-determination than students with low GPAs. Results of this study reveal important fields of intervention, especially for students with disabilities.
Keywords: self-determination; vocational education; students with disabilities; academic achievement; gender